2012
DOI: 10.1111/j.1365-2443.2011.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mitochondrial transcription in fission yeast with ETB, an inhibitor of HSP60, the chaperone that binds to the mitochondrial transcription factor Mtf1

Abstract: Mtf1 has been characterized as a mitochondrial transcription factor and is shown to regulate mitochondrial transcription. Mtf1 has an additional function as a transcription factor for the nuclear gene srk1 in fission yeast. Hsp60 has been linked to a variety of important cellular functions such as apoptosis and the immune response. It functions mainly as a molecular chaperone that assists correct protein folding in the mitochondrion. Epolactaene tertiary butyl ester (ETB) is an inhibitor of human Hsp60 that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…One of the most studied Hsp60 inhibitors is epolactaene, a bacterial metabolite which inhibits the folding activity of human Hsp60, through covalent binding to Cys442 [ 79 ]. Epolactaene derivatives, such as the tertiary butyl ester ETB ( Figure 3 ), were also active [ 80 ] and SAR studies demonstrated that both the cyclic amide (lactam) and the α,β-unsaturated ketone are critical moieties for inhibiting the chaperone activity of Hsp60 [ 81 ]. An in-silico study suggested a putative mode of action for epolactaene, revealing the opening of a binding pocket in proximity of Cys442 after ATP occupies its binding site and that epolactaene covalently binds thiol moiety of Cys 442 through attack at C14 and epoxide ring-opening [ 82 ].…”
Section: Hsp60mentioning
confidence: 99%
“…One of the most studied Hsp60 inhibitors is epolactaene, a bacterial metabolite which inhibits the folding activity of human Hsp60, through covalent binding to Cys442 [ 79 ]. Epolactaene derivatives, such as the tertiary butyl ester ETB ( Figure 3 ), were also active [ 80 ] and SAR studies demonstrated that both the cyclic amide (lactam) and the α,β-unsaturated ketone are critical moieties for inhibiting the chaperone activity of Hsp60 [ 81 ]. An in-silico study suggested a putative mode of action for epolactaene, revealing the opening of a binding pocket in proximity of Cys442 after ATP occupies its binding site and that epolactaene covalently binds thiol moiety of Cys 442 through attack at C14 and epoxide ring-opening [ 82 ].…”
Section: Hsp60mentioning
confidence: 99%
“…Mtf1 has been characterized as a mitochondrial transcription factor and shown to regulate mitochondrial transcription. In fission yeast, MTF1 binds to Hsp60 in vivo and in vitro , and ETB inhibits the association of MTF1 and Hsp60, which represses mitochondrial transcription ( 32 ). The present study found that MTF1 had a significant positive correlation with mast cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, other derivatives of epolactaene (9), such as the epolactaene tertiary butyl ester (ETB) (10), were shown to target mitochondrial transcription [135]. A structure-activity relationship analysis performed on epolactaene derivatives demonstrated that both the cyclic amide (lactam) and the '-" unsaturated ketone are critical moieties for inhibiting the chaperone activity of HSP60 [129].…”
Section: Hsp60 Inhibitors and Their Potential Applications In Alzheimmentioning
confidence: 99%